Diseminasi Teknologi Padi IPB untuk Memperkuat Desa Lumbung Padi di Desa Pangumbahan Kabupaten Sukabumi - Ahmad Junaedi; Hajrial Aswidinnoor; Heni Purnamawati; Fitrianingrum Kurniawati; Sherly Eka Maulidiya; Muhammad Syukur (Institut Pertanian Bogor, 2025)
The IPB rice technology dissemination program implemented in Pangumbahan Village, Ciracap District, Sukabumi Regency, aimed to improve the knowledge and skills of fostered partner farmers through technology transfer and innovation to increase land utilization and support the intensification of rice production. This service activity involved four active IPB students, four IPB lecturers, and the Sabilulungan Farmer Group Union (Gapoktan) as fostered partners. The method of activity implementation consisted of observation, mapping of potential and problems, program implementation, and monitoring and evaluation of the program. The implementation of the IPB rice technology dissemination program began with field observations, including a survey of field conditions. Focus group discussion (FGD) activities were conducted to map the potential and problems in the community. Program implementation consisted of training and assistance in transferring technology and innovation in rice cultivation. Monitoring and evaluation were conducted through in-depth interviews and discussions with the assisted farmers. Through the establishment of demonstration plots of IPB 3S and IPB 9G rice varieties, the community can increase its knowledge and skills regarding the development of their commodities. The implementation of technology transfer through training and practice of the IPB Prima rice cultivation technique can encourage more efficient and productive rice cultivation.